Exploring the hidden connections between information channel use and pro-environmental behavior among recreational anglers of the shore-based shark fishery in Florida, United States - Guay, Jessika D.; Brooks, Jill L.; Chapman, Jacqueline M.; Medd, Hannah; Cooke, Steven J.; Nguyen, Vivian M. (Frontiers in Communication, 2023)
Shore-based shark fishing in Florida is a relatively low-cost and easy-access fishery which attracts a wide variety of experienced and inexperienced anglers leading to concerns about proper handling methods of captured fish that are released either voluntarily or to comply with regulations. Proper handling methods can help reduce post-release mortality among sharks, many of which are threatened with extinction. Therefore, we considered proper handling methods as a pro-environmental behaviour, which has been linked with the use of different information channels to increase conservation knowledge. We used data from an online questionnaire to understand where anglers of this fishery obtain information about fishing skills with a particular focus on fish handling techniques and best practices for catch-and-release. Then we included their main information channels in a series of hierarchical regression models with perceived conservation knowledge and support for fishery management to explain pro-environmental behaviour regarding shark conservation. We found that most anglers learned about shore-based shark fishing through interpersonal communications with friends and family, but typically use the internet to learn more about fishing skills. While information channel use was not significantly associated with pro-environmental behaviour, it was significantly associated with support for fisheries management, which in turn was associated with pro-environmental behaviour among respondents. These findings can inform public educational outreach efforts to spread awareness of proper handling techniques and reduce instances of post-release mortality in sharks.